A REVIEW ON ANGIOGENESIS ASSAYS (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The angiogenesis activity was involved in many physiological and pathological conditions. The research on angiogenesis activity was increased and many new methods are come for the evaluation of the angiogenesis activity. Previously Robert Auerbach et al., described the methods used for the evaluation of angiogenesis activity. We added some more techniques to that which are currently used for the evaluation of angiogenesis activity. Some of ischemic models are also used for the evaluation of angiogenesis like hindlimb ischemia model, coronary artery ligation model and Langendorff isolated model. Some of the new methods are introduced for the evaluation of inflammatory angiogenesis i.e. sponge granuloma angiogenesis assay. The CAM assay, corneal angiogenesis assay and matrigel plug assays are used for the evaluation of both angiogenic and anti-angiogenic agents. We also described some of the quantification techniques which are easily performed in laboratory like capillary density and estimation of hemoglobin in Matrigels.